Trauma Indices for Prediction of Acute Respiratory Distress Syndrome - Afshar, Majid (J Surg Res, 2015)
BACKGROUND: A myriad of trauma indices have been validated to predict probability of trauma survival. We aimed to compare the performance of commonly used indices for the development of the Acute Respiratory Distress Syndrome (ARDS). MATERIALS AND METHODS: Historic, observational cohort study of 27,385 consecutive patients admitted to a statewide referral trauma center between July 11, 2003 and October 31, 2011. A validated algorithm was adapted to identify patients with ARDS. Each trauma index was evaluated in logistic regression using the area under the receiver operating characteristic curve. RESULTS: The case-rate for ARDS development was 5.8% (1,594). The receiver operating characteristics for ISS had the best discrimination and had an area under the curve of 0.88 (95% CI 0.87–0.89). Glasgow coma score (0.71, 95% CI 0.70–0.73), A Severity Characterization of Trauma (0.86, 95% CI 0.85–0.87), Revised Trauma Score (0.71, 95% CI 0.70–0.72) and thorax Abbreviated Injury Score (0.73, 95% CI 0.72–0.74) performed worse (p<0.001) and Trauma and Injury Severity Score (0.88, 95% CI 0.87–0.88) performed equivocally (p=0.51) in comparison to ISS. Using a cutoff point ISS greater than or equal to 16, sensitivity and specificity were 84.9% (95% CI 83.0%–86.6%) and 75.6% (95% CI 75.1%–76.2%), respectively. CONCLUSIONS: Among commonly used trauma indices, ISS has superior or equivocal discriminative ability for development of ARDS. A cutoff point of ISS greater than or equal to 16 provided good sensitivity and specificity. The use of ISS greater than or equal to 16 is a simple method to evaluate ARDS in trauma epidemiology and outcomes research.